Electrosynthesis of Sugar Derivatives - Santiago, C. C. (2024)
The last decades have witnessed significant advances in the synthesis of bioactive carbohydrates. As in all fields of organic synthesis, the search for more environmentally friendly alternative synthetic methods is a current and expanding concern. Consequently, electrochemical organic synthesis has emerged as an efficient and sustainable methodology. Herein, we present recent developments in the synthesis of glycosides and other carbohydrate derivatives using electrochemical methods. Diverse natural and synthetic O-, S-, and C-glycosides were obtained using new approaches for the electrochemical activation of sugar precursors. The reported derivatives exhibited wide structural diversity on both the sugar moiety and the aglycone, revealing the great potential of the electrochemical methods.